The Representation of Self Defense Mechanism in Russell’s My Dark Vanessa Novel - Nuria Fafi Rohmatin, Nuria (Karangan: Jurnal Bidang Kependidikan, Pembelajaran, dan Pengembangan, 2024)
This research aims to analyze the image of a girl as reflected through the main character, namely Vanessa Wye, in the novel entitled My Dark Vanessa by Kate Elizabeth Russel. This research focuses on elaborating the kind of defense mechanisms that is used by the character in defense her life in future. In elaborating this case, the researcher applies Sigmund Freud's Psychoanalytic theory that focuses on defense mechanism through context-oriented approach. Therefore, this research attempts to seek the evidence in analyzing the issue by the sentence, narration, description and everything that are depicted in the novel to fulfill the adequate data in this research as well. Furthermore, the findings in this research points out that there are 10 kind of self-defense mechanism that is used by the main character named Vanessa as reflected in the novel, namely; denial, sublimation, reaction formation, displacement, intellectualization, regression, repression, rationalization, projection, and compartmentalization. The issue of defense mechanism in this novel begins from the representation of the relationship between Vanessa and Strane that had an unnatural love affair and abuse, which caused the young girl to have deep trauma due to the abuse, however, this love affair led to sexual harassment, it is suspected that many other victims after Vanessa experienced the same case as Strane. Vanessa was traumatized by this incident and tried to get up with the strength that was within her.